Building Sustainability in Agribusiness: Innovation-Based Business Development Strategy - Malta (Global Writing Academica Researching & Publishing, 2025)
This study aims to explore innovation-based agribusiness development strategies to support sustainability in West Java. The main focus of this study is to identify the innovations implemented, the development strategies carried out, and the supporting and inhibiting factors in the innovation process. The research methods used include in-depth interviews with agribusiness actors, surveys of stakeholders, and case studies on businesses that have successfully adopted innovative practices. The results of the study indicate that technological innovations such as smart irrigation systems, precision agriculture, and the use of drones play an important role in increasing productivity and efficiency. Business diversification strategies and strengthening partnership networks have proven to be able to expand market access and increase economic resilience. There are challenges such as limited access to technology and capital, as well as regulations that are not yet fully supportive, which are the main obstacles to the implementation of innovation. The implications of these findings emphasize the need for cross-sector collaboration, increasing human resource capacity, and adaptive policy support to ensure the sustainability of agribusiness in West Java, the agribusiness sector has the potential to become a driving force for sustainable development that is highly competitive with a holistic and innovative approach.